POLA PENGEMBANGAN BUDAYA AKADEMIK PADA PENDIDIKAN TINGGI ISLAM NEGERI ACEH - Basri Basri; Mahyiddin Mahyiddin; Andhika Jaya Putra; Wahidah Wahidah (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2023)
This article discussed the university's academic development in Aceh Islamic higher education. According to this, the Islamic higher education in Aceh existed in the reality of the cultural system between the local and global situations as competed at the international level. This article was phenomenological research conducted by applying focus group discussion with lecturers, faculty, and university staff. Observation was utilized to collect the data. As a result, the academic culture played an essential role in varying degrees. As part of human resources, the academic culture identified the support for university-level more need assistance to answer all education problems in Aceh.